Inhibiting CK2 among Promising Therapeutic Strategies for Gliomas and Several Other Neoplasms - Emanuela B. Pucko; Robert P. Ostrowski (MDPI AG, 2022)
In gliomas, casein kinase 2 (CK2) plays a dominant role in cell survival and tumour invasiveness and is upregulated in many brain tumours. Among CK2 inhibitors, benzimidazole and isothiourea derivatives hold a dominant position. While targeting glioma tumour cells, they show limited toxicity towards normal cells. Research in recent years has shown that these compounds can be suitable as components of combined therapies with hyperbaric oxygenation. Such a combination increases the susceptibility of glioma tumour cells to cell death via apoptosis. Moreover, researchers planning on using any other antiglioma investigational pharmaceutics may want to consider using these agents in combination with CK2 inhibitors. However, different compounds are not equally effective when in such combination. More research is needed to elucidate the mechanism of treatment and optimize the treatment regimen. In addition, the role of CK2 in gliomagenesis and maintenance seems to have been challenged recently, as some compounds structurally similar to CK2 inhibitors do not inhibit CK2 while still being effective at reducing glioma viability and invasion. Furthermore, some newly developed inhibitors specific for CK2 do not appear to have strong anticancer properties. Further experimental and clinical studies of these inhibitors and combined therapies are warranted.